2021
DOI: 10.3892/ol.2021.13081
|View full text |Cite
|
Sign up to set email alerts
|

Membranous CD44v6 is upregulated as an early event in colorectal cancer: Downregulation is associated with circulating tumor cells and poor prognosis

Abstract: Previous studies have reported that CD44 variant 6 (CD44v6) and metastasis-associated protein 1 (MTA1) are contributing factors to cancer progression. The present study aimed to evaluate the expression profiles for associations with patients' demographic data, clinicopathological characteristics, the presence of partial epithelial-to-mesenchymal transition (pEMT), metastatic potential based on the presence of CK20 + CEA + CXCR4 + circulating tumor cells (CTCs) and prognosis (median follow-up, 45 months). Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Systematic assessment of the prognostic impact of mCD44v6 protein revealed that the loss of mCD44v6 is associated with lymph node metastasis and adverse prognosis with the reduction in mCD44v6 expression from the center of the tumor to its invasive front [7,29]. Downregulation of mCD44v6 is associated with the presence of circulating tumor cells (CTCs) [30].…”
Section: Discussionmentioning
confidence: 99%
“…Systematic assessment of the prognostic impact of mCD44v6 protein revealed that the loss of mCD44v6 is associated with lymph node metastasis and adverse prognosis with the reduction in mCD44v6 expression from the center of the tumor to its invasive front [7,29]. Downregulation of mCD44v6 is associated with the presence of circulating tumor cells (CTCs) [30].…”
Section: Discussionmentioning
confidence: 99%